Knowledge and Attitude Regarding Care of Elderly People among Nursing Students in a Nursing College of Pokhara - Shrestha, Pragya; Adhikari, Anita; K.C., Reshma (Academia Research Journal, 2026)
With the increasing elderly population with chronic illness, an increase in physical dependency, nurses should be knowledgeable and have a positive attitude toward elderly care. A descriptive study was conducted to determine the knowledge and attitudes towards elderly care among 68 nursing students from a nursing college in Pokhara using an enumerative sampling technique. A self-administered semi-structured questionnaire was used to assess knowledge on elderly care, and a 5-point Likert scale was used to identify attitudes towards elderly care. The data were analyzed using descriptive and inferential statistics with the Statistical Package for the Social Sciences (SPSS) software version 20. The study showed that 60.30% of respondents had high knowledge, and 54.40% of the respondents had a negative attitude towards elderly care. Likewise, 95.60% of respondents knew that listening and giving time to talk with elderly people, and 60% respondents strongly agree that they feel good about taking care of elderly people. More than half of the respondents had high knowledge, while less than half had a positive attitude towards elderly care. The types of family, elderly members in the family, and experience of elderly care were not significantly associated with knowledge and attitudes regarding the care of elderly people. Therefore, continuing education for nursing students on elderly care should be conducted to enhance their knowledge and positive attitude toward elderly care.